Guide d'écriture inclusive - Institut de recherches et d'études féministes (FéminÉtudes, 2020)
FéminÉtudes est une revue étudiante, féministe et multidisciplinaire. La revue est née en 1995 de l’initiative d’étudiantes féministes dans l’intérêt de partager leurs recherches et de créer un groupe affinitaire. La revue est dirigée par des collectifs de rédaction bénévoles et autogérés, et soutenue par l’Institut de Recherches en Études Féministes (IREF) de l’Université du Québec à Montréal. Au fil des ans, FéminÉtudes a réussi à se bâtir une réputation et une légitimité dans le champ de la recherche en études féministes, tout en offrant une tribune au travaux et aux réflexions de dizaines d’étudiant.e.s. Au-delà de la recherche, c’est également pour l’avancement des luttes féministes que FéminÉtudes souhaite continuer à grandir.
Keywords: 2000 à aujourd'hui; amériques; approches et analyses; féminétudes; genre; histoire et politique; identités LGBTQIA2+; intersectionnalité; militance; outils; ouvrages de références; périodes historiques; queer; québec; ressource en ligne; régions géographiques; thématiques; écriture inclusive

Intersectionality in feminist and queer movements: Confronting privileges - Evans, Elizabeth (Routledge, 2020)
Examining the ways in which feminist and queer activists confront privilege through the use of intersectionality, this edited collection presents empirical case studies from around the world to consider how intersectionality has been taken up (or indeed contested) by activists in order to expose and resist privilege. The volume sets out three key ways in which intersectionality operates within feminist and queer movements: it is used as a collective identity, as a strategy for forming coalitions, and as a repertoire for inclusivity. The case studies presented in this book then evaluate the extent to which some, or all, of these types of intersectional activism are used to confront manifestations of privilege. Drawing upon a wide range of cases from across time and space, this volume explores the difficulties with which activists often grapple when it comes to translating the desire for intersectionality into a praxis which confronts privilege. Addressing inter-related and politically relevant questions concerning how we apply and theorise intersectionality in our studies of feminist and queer movements, this timely edited collection will be of interest to students and scholars from across the social sciences and humanities with an interest in gender and feminism, LGBT+ and queer studies, and social movement studies.
Keywords: LGBTQIA2+; approches et analyses; identités LGBTQIA2+; intersectionnalité; militance; outils; ouvrages de références; privilèges; queer; ressource en ligne; systèmes d'oppressions; thématiques